A migration-driven model for the historical spread of leprosy in medieval Eastern and Central Europe - Donoghue, Helen D.; Michael Taylor, G.; Marcsik, Antónia; Molnár, Erika; Pálfi, Gyorgy; Pap, Ildikó; Teschler-Nicola, Maria; Pinhasi, Ron; Erdal, Yilmaz S.; Velemínsky, Petr; Likovsky, Jakub; Belcastro, Maria Giovanna; et al. (Infection, genetics and evolution, 2015)
•32 skeletal remains from 16 sites in 7 countries had physical evidence of leprosy.•26 individuals harbored Mycobacterium leprae ancient DNA and/or lipid biomarkers.•Avars from Central Asia were linked with 6th–8th century European leprosy burials.•We confirmed the earliest known leprosy cases in Southern Hungary and Austria.•Ancient DNA showed that six individuals had leprosy co-infected with tuberculosis. Leprosy was rare in Europe during the Roman period, yet its prevalence increased dramatically in medieval times. We examined human remains, with paleopathological lesions indicative of leprosy, dated to the 6th–11th century AD, from Central and Eastern Europe and Byzantine Anatolia. Analysis of ancient DNA and bacterial cell wall lipid biomarkers revealed Mycobacterium leprae in skeletal remains from 6th–8th century Northern Italy, 7th–11th century Hungary, 8th–9th century Austria, the Slavic Greater Moravian Empire of the 9th–10th century and 8th–10th century Byzantine samples from Northern Anatolia. These data were analyzed alongside findings published by others. M. leprae is an obligate human pathogen that has undergone an evolutionary bottleneck followed by clonal expansion. Therefore M. leprae genotypes and sub-genotypes give information about the human populations they have infected and their migration. Although data are limited, genotyping demonstrates that historical M. leprae from Byzantine Anatolia, Eastern and Central Europe resembles modern strains in Asia Minor rather than the recently characterized historical strains from North West Europe. The westward migration of peoples from Central Asia in the first millennium may have introduced different M. leprae strains into medieval Europe and certainly would have facilitated the spread of any existing leprosy. The subsequent decline of M. leprae in Europe may be due to increased host resistance. However, molecular evidence of historical leprosy and tuberculosis co-infections suggests that death from tuberculosis in leprosy patients was also a factor.